Ponding Instability of Air-Supported Elastic Spherical Membranes - Ahmadi, G.; Glockner, P.G. (Engineering Transactions, 1983)
The problem of collapse by bonding of air-supported spherical membranes subjected to a central load is considered. Linearly elastic and two-way membrane action is assumed. The equilibrium of the spherical cap is analysed and the equations for the determination of the critical central weight for the onset of collapse are derived. Numerical solutions are obtained for a range of internal pressures, elastic moduli, height/span ratios and radii of curvature. Results from the present study for large elastic moduli are compared with previously obtained experimental data and theoretical predictions [8, 11].